2017
DOI: 10.3390/md15090288
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of Marine-Derived Sulfoglycolipids, a New Class of Molecular Adjuvants

Abstract: Vaccines play a primary role in the protection of human health by preventing infectious and chronic diseases. Recently we have reported 1,2-O-distearoyl-3-O-β-d-sulfoquinovosylglycerol (β-SQDG18), here named Sulfavant A (1), which shows promising properties as a new molecular adjuvant in in vitro and in vivo tests. In the present manuscript, we provide full details about a synthetic strategy for the preparation of 1, including a discussion of chemical determinants of the activity and the major technical hurdle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 32 publications
(39 reference statements)
2
30
0
Order By: Relevance
“…Sulfavants are bioactive molecules able to induce DC maturation and trigger an adaptive immune response in vivo [13][14][15]. The activity of these products is largely dependent on the formation of colloidal particles under aqueous conditions [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sulfavants are bioactive molecules able to induce DC maturation and trigger an adaptive immune response in vivo [13][14][15]. The activity of these products is largely dependent on the formation of colloidal particles under aqueous conditions [12].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we recently characterized β-sulfoquinovosyl-diacyl glycerols (β-SQDGs) as a novel class of vaccine adjuvants collectively named Sulfavants. These synthetic molecules were inspired by natural and marine α-sulfoquinovosyl-diacylglycerols (α-SQDGs) occurring as membrane constituents in photosynthetic organisms [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Miralto et al [14] reported that diatom unsaturated aldehydes had antiproliferative effects on Caco-2 cells derived from a human colon adenocarcinoma; Sansone et al [15] showed similar effects on colon COLO-205 and lung A-549 adenocarcinoma cell lines. Manzo et al [16,17] claimed immunomodulatory activity of Sulfavant A, a synthetic glycolipid, which is a prototype for a new class of molecular vaccine adjuvants based on a sulfolipid skeleton and structurally inspired by natural α-D-sulfoquinovosyl-diacylglycerols purified from the marine diatom Thalassiosira weissflogii . Furthermore, from the same diatom species, very recently, a novel phosphatidylmonogalactosylglycerol lipid (PGDG) rich in polyunsaturated fatty acids (PUFA) was isolated, which showed immunostimulatory activity mediated by Toll-like receptor-4 in dendritic cells [18].…”
Section: Introductionmentioning
confidence: 99%